Preferred Competencies for Tourism and Hospitality Graduates: Evidence from Longitudinal Tracer Studies - Putra, Fajar Kusnadi Kusumah; Saepudin, Pudin; Utami, Ni Gusti Made Kerti (Journal of Technical Education and Training, 2022)
This paper reports on the multi-cohort tracer studies about graduates’ perception (inserted) of employability, competencies, and job-specific skills in the field of tourism and hospitality management. Mixed-methods research was designed to explore graduates’ perceptions of the preferred competencies using online surveys. 1694 tourism and hospitality graduates participated in this study, and data were collected using a longitudinal design involving three cohorts. The results of this study show that three competencies constitute the critical skills required in future employment for tourism and hospitality management graduates namely fundamental, functional and professional competencies. The findings shed new light on the vocational education and training (VET) preferred competencies, especially from the perspective of the graduates in the field of tourism and hospitality management. This study also suggested that preferred graduates’ job competencies for the tourism and hospitality sectors can integrate with collaboration strategy during internship and industry-related certification programs. In the context of learning experiences, this study also found that tracer studies play a crucial role as the initial stage for developing higher education curricula relevant to tourism and hospitality management courses.